OVERVIEW OF ATHLETE BADMINTON GAME PATTERNS - Harahap, Agustin Sastrawan (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This study aims to determine the quality of badminton games with the right play patterns from professional players in the 2016 All England world championship with the formulation of a research problem that is how the shape of the badminton athlete's game pattern at the All England world championship. Research with a qualitative approach to the acquisition of data in the form of writings (typing) from the match notes, then the data is described to answer the problem formulation. The research activity is to analyze the development of world players to be able to learn and apply the pattern of the game to athletes. The results obtained that only 2 badminton game patterns are most used by athletes to win world championship, namely 1) defensive game patterns: lob-lob-chop-net-lob-smash-net-net (defen), 2) attacking game patterns : Lob-chop-net-lob-net-drive-lob-smash. The 2016 All England World Champion by Lin Dan, with the technique of the game trying to understand the opponent's game characters first at the beginning of the game and understand the opponent's weaknesses, then determine the right game pattern at the match.